The Effect of Dental Anxiety Levels of Medical Faculty Students on Oral Hygiene Behaviors - Ezgi Ağadayı; Seher Karahan (Cumhuriyet University, 2022)
Aim: Aimed to evaluate the effect of dental anxiety levels of students at Sivas Cumhuriyet University Faculty of Medicine on oral hygiene behaviors. Materials and Methods: It is descriptive, cross-sectional study and carried out between September-October 2021. It was applied online to 216 volunteers from class I-V students. Students were asked about their sociodemographic characteristics, oral hygiene behaviors and Corah Dental Anxiety Scale(C-DAS). The C-DAS questionnaire is in 5-point Likert type consisting of 4 questions (Min:4-max:20 points). Analyzes were made with the SPSS 25 program. Descriptive statistics, independent sample T-test were performed. Results: 50%(n=108) of the students were women. 78.2%(n=169) had never smoked. 33.3%(n=72) of them started brushing regularly before age of six. 58.8%(n=127) were brushing their teeth at least twice a day. The rate of brushed their teeth correctly was 49.5% (n=107). Only 24.5%(n=53) of the students changed their toothbrush every three months. Students' use of additional dental hygiene tools other than toothbrushes respectively; toothpick (37.5%, n=81), dental floss (32.4%, n=70), mouthwash (26.9%, n=58), interface brush (6%, n=13), miswak (3.7%, n=8). The mean C-DAS score was 8.8±3.7(min:4-max:20). The mean score was significantly higher for female students (9.5±3.7) than the males (8.0±3.5) (p=0.004) and those who had a toothache (9.5±4.1) in the last year than the others (8.1±3.2) (p=0.007). There was no significant difference between C-DAS score and brushing teeth twice a day or more(p=0.556). There was no significant difference between the use of additional dental hygiene tools and C-DAS score(p=0.280). Conclusion: Dental anxiety was found to be higher in women and those who had toothache in the last year. It was determined that anxiety did not affect the dental hygiene behavior.